Botswana : 2017 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights the recovery of Botswana's economic activity in 2016: real GDP growth was 4.3 percent. Mineral production has remained subdued, but diamond sales rebounded as conditions in the global market began to improve. Nonmining activities also expanded, supported by accommodative fiscal and monetary policies and reforms in the electricity sector. Year-over-year inflation has remained stable near the lower band of the Bank of Botswana's inflation objective range of 3-6 percent; the 12-month rate of inflation was 3.5 percent in May 2017. The fiscal position has also improved as the deficit narrowed from 4.6 percent of GDP in fiscal year 2015/16 to about 1 percent of GDP in 2016/17.